Fur Seals and Other Pinnipeds - Piasetsky, Lome; World Book, Inc. (Chicago : World Book, 2000)
Questions and answers explore the world of pinnipeds, with an emphasis on seals.
Includes index.
Keywords: Seals (Animals) -- Juvenile literature; Pinnipedia -- Juvenile literature